2015
DOI: 10.1016/j.chroma.2015.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Inverse gas chromatography for natural fibre characterisation: Identification of the critical parameters to determine the Brunauer–Emmett–Teller specific surface area

Abstract: A c c e p t e d M a n u s c r i p t  BET specific surface areas were determined by Inverse Gas Chromatography for samples of flax, kenaf and cellulose fibres.  The effect of experimental conditions on the BET surface area values were investigated.  Bast fibres showed a large variability within a batch compared to synthesised cellulose fibres.  An experimental procedure to determine the BET surface area values for natural fibres is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 32 publications
0
22
2
Order By: Relevance
“…Also, based on the measurements of the isothermal nitrogen sorption for the composites, we could obtain the specific surface area of 55.8 m 2 ⋅g −1 for the composites, using the Brunauer‐Emmett‐Teller (BET) equation . Finally, the magnetic hysteresis loop was measured at room temperature for the nZVI/CSs, as shown in Figure .…”
Section: Resultscontrasting
confidence: 63%
“…Also, based on the measurements of the isothermal nitrogen sorption for the composites, we could obtain the specific surface area of 55.8 m 2 ⋅g −1 for the composites, using the Brunauer‐Emmett‐Teller (BET) equation . Finally, the magnetic hysteresis loop was measured at room temperature for the nZVI/CSs, as shown in Figure .…”
Section: Resultscontrasting
confidence: 63%
“…BET surface area was 1.56±0.02 m²/g. This result is higher than those reported by Legras et al [45] for macroporous cellulose BioMid ® and kenaf fibers. In addition, the structure of the PFS fibers could mean that the immobilization of trypsin could be done only on the monolayer of the carrier.…”
Section: Adsorption and Superficial Areacontrasting
confidence: 70%
“…Previous studies also reported the adsorption of xyloglucan on cellulose nanocrystals (Dammak, Quémener et al, 2015;Gu & Catchmark, 2013;Lopez et al, 2010) with a maximal adsorption between 98-333 mg XG /g cellulose . The higher amount of adsorbed XG on cellulose nanocrystals as substrates is due to the much higher specific surface area of CNC that range from 150 to 800 m²/g (Brinkmann et al, 2016;Habibi, 2014), as compared to that of flax fibres, roughly 1 m²/g (Bismarck et al, 2002;le Duigou, Bourmaud, Balnois, Davies, & Baley, 2012;Legras, Kondor, Heitzmann, & Truss, 2015;Müssig, Fischer, Graupner, & Drieling, 2010), even if fibre swelling could contribute to improve specific surface area. Fig.…”
Section: Adsorption Isothermsmentioning
confidence: 99%